Agrobacterium-mediated Genetic Transformation of Two Varieties of Jute (Corchorus capsularis L.) - Sarker, Rakha Hari; Al-Amin, G.M.; Hassan, Fathi; Hoque, M.I. (Plant Tissue Culture and Biotechnology, 2009)
Transformation experiments were carried out using different explants of two varieties of white jute (Corchorus capsularis L.), namely, CVL-1 and CVE-3 with Agrobacterium tumefaciens strain (LBA4404/pBI121) containing the GUS and nptII genes. Maximum transformation ability was obtained from petiole-attached cotyledons and mature embryo explants. Kanamycin at a concentration of 200 mg/l was found optimum for selection of transformed shoots developed from mature embryos. Histochemical assay revealed the stable expression of the GUS gene within the various tissues of transformed plantlets. Stable integration of GUS and nptII genes were confirmed by PCR analysis of genomic DNA isolated from these transformed shoots. Key words: Jute, Transformation, GUS expression, PCR analysis D.O.I. 10.3329/ptcb.v18i1.3245 Plant Tissue Cult. & Biotech. 18(1): 7-16, 2008 (June)